ALPOMISH VA KUNTUG’MISH DOSTONLARI ASOSIDA KOMPLEKS ETNOTURIZM MAHSULOTINI YARATISH HAMDA UNI XALQARO BOZORGA EKSPORT QILISHNING NAZARIY TAHLILI - TILOVMURODOV SHOHJAHON (TADQIQOTLAR, 2026)
Abstarct: This study provides an in-depth analysis of the theoretical, institutional, and economic mechanisms for developing a comprehensive ethnographic tourism product based on epic narratives and exporting it to the international market.